Pemberdayaan Ekonomi Perempuan melalui Usaha Penjualan Tabaro Dange - Rika Suprapty (BISMA (Bisnis dan Manajemen), 2018)
ABSTRACT This study aims to find out how the method of economic empowerment of women through the sale of Tabaro Dange along the Palu Culinary Coast and how the strategy of women's economic empowerment through the sale of Tabaro Dange along the Palu Bay Culinary Area. This research uses qualitative or naturalistic approach with constructive paradigm. The research was conducted in the area along the bay coast of Palu City (Taman Ria, Cumi-Cumi road, and Cut Meutia road). Data collection techniques used in this study are interviews, observation and documentation. The result of the research shows that female economic empowerment method that can be applied through selling Tabaro Dange along Palu Bay Beach Culinary Area is a combination of PLA empowerment method (sharing and discussion about women economic empowerment through selling tabaro dange) and Tatap Muka, where this method is considered most adapted to the condition of the informant. This method is also known as the method of "learning by doing" or learning while working, so the implementation in the field of researchers do sharing and discussion while the informant serves the sales of tabaro dange so it is more efficient and effective and does not interfere with the activity of the informant. The women empowerment strategy applied to the selling business of tabaro dange conducted by the researcher is to arrange the data collection instrument; building understanding, commitment to encourage self-reliance of individuals, families and communities and preparing information systems, developing systems of analysis, intervention, monitoring and evaluation of individual, family and community empowerment.  Keywords: Women Economic Empowerment, Tabaro Dange